PENGARUH ASPEK PERSONALITAS DAN MODAL HUMANIAL TERHADAP SUKSES WIRAUSAHAWAN MUDA DI KOTA SEMARANG - M. Agung Widyowanto; Ribut Musprihadi (Media Ekonomi dan Manajemen, 2017)
ABSTRACT               The success of entrepreneurship is influenced by many aspects, especially aspects of personality and humanial capital, which in this study manifested in the variable need for achievement, locus of control, knowledge of entrepreneurship and entrepreneurial experience.The purpose of this study was to analyze the influence of need for achievement, locus of control, knowledge of entrepreneurship and entrepreneurial experience to the success of young entrepreneurs.               Respondents are young entrepreneurs in Semarang some 100 people, selected by purposive sampling. Analysis of data using test validity, reliability, classical assumption (normality, multicollinearity, heteroscedasticity), Test kindness model (the F test and the coefficient of determination) and hypothesis test (t test).               The results showed that the need for achievement, locus of control, knowledge of entrepreneurship and entrepreneurial experience positive and significant impact on the success of young entrepreneurs. Keywords: personality aspects, capital  humanial, successful young entrepreneurs